Pengaruh Penggunaan Dompet Digital Terhadap Mental Accounting pada Remaja di Kota Medan - Manurung, Raudah Azzahra; Silalahi, Purnama Ramadani (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
A digital wallet, or electronic wallet, is a type of electronic payment account that allows users to save money for future transactions. According to Thaler (1985), mental accounting is a set of cognitive operations that individuals and households use to code, classify, and evaluate financial activities. The purpose of this study was to find out how the use of digital wallets affects the mental accounting of teenagers in Medan. This study uses a descriptive method, a questionnaire distribution method with intentional simplification, a quantitative survey approach using criteria for adolescents aged 20-24 years with a sample of 100 people, and a test tool using SPSS 25. The results of this study explain when digital wallet (X) increases, mental accounting (Y) also increases, and conversely, when digital wallet (X) decreases, mental accounting (Y) also decreases.